Estimation model of weight of steel in reinforced concrete building with seismic design in Malaysia - Adiyanto, Mohd Irwan; Ahmad, Saffuan Wan; Ali, Mohammad Idris; Ramli, N. I.; Chin, S. C.; Taksiah, A. Majid; Azlan, Adnan; Syed Abdul Haris, Syed Mustafa (2020)
Generally, reinforced concrete buildings in Malaysia were built and used widely compared to steel, timber, and masonry wall system. Majority reinforced concrete design practice in Malaysia had been conducted without seismic consideration by referring to BS 8110. On 5th June 2015, a moderate earthquake with magnitude Mw5.9 was occurred in Sabah. The epicentre was located at 16 km northwest from Ranau. The tremors were felt in Kundasang, Ranau, Tambunan, Pedalaman, Tuaran, Kota Kinabalu, and Kota Belud. A lot of damages had been reported on residential, school, mosque, temple, and commercial buildings. In medium – to – high risk earthquake zones, the Malaysian Public Work Department had suggested that it is worthwhile to consider seismic design input for new buildings. From economical view, it is interesting to study the effect of seismic design on cost of construction material and factors which influencing the cost. Hence, this research work investigated the effect of seismic design on the amount of steel used as reinforcement in reinforced concrete buildings. This research focused to low rise reinforced concrete buildings as models covering various function namely as hospital, office, school, and multipurpose hall. A total of four seismic design parameters namely as reference peak ground acceleration, αgR soil type, concrete grade, and ductility class had been considered in analysis and design process. Based on results, it can be concluded that the total weight of steel reinforcement increases as the value of reference peak ground acceleration, αgR increases. Soil type also influencing the total weight of steel reinforcement. Different soil type caused the total weight of steel reinforcement increased around 1.16 to 2.11 times higher compared to the nonseismic design. Besides, the concrete grade and ductility class also influencing the total weight of steel reinforcement. Lower concrete grade required higher amount of steel reinforcement. In regions with higher seismicity, ductility class medium is preferable for more economical design.